Capital Budgeting: Peran Akuntansi Manajemen dalam Menentukan Kelayakan Investasi Jangka Panjang - Muhammad Tavif Al Muzacky; Mukhtaruddin Mukhtaruddin (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study aims to analyze the role of management accounting in supporting the capital budgeting process and determining long-term investment feasibility. The research employs a qualitative approach using the Systematic Literature Review (SLR) method by analyzing 20 scientific articles indexed in Scopus and SINTA published between 2021 and 2025. The research process was conducted through literature identification, article selection based on inclusion and exclusion criteria, classification of research themes, and content analysis to obtain a comprehensive synthesis of research findings. The results indicate that management accounting plays an important role in providing strategic information to support investment evaluation, risk control, and long-term decision-making. In addition, the integration of digital technologies such as big data analytics and modern information systems has proven to improve the quality of the capital budgeting process and the effectiveness of investment decision-making. However, the implementation of management accounting practices still faces several challenges, including limited managerial competence, high information costs, and behavioral factors influencing investment decisions. Based on the Contingency Theory perspective, the effectiveness of management accounting and capital budgeting practices is strongly influenced by the suitability between the systems used and the organizational conditions as well as the business environment. This study is expected to provide theoretical and practical contributions to the development of management accounting practices in supporting more effective and sustainable investment decisions.